The external debt and economic growth nexus: empirical evidence in Ghana. - Najib, ibn Abdullahi Hassan (KNUST, 2025)
A Thesis Submitted To The Department Of Accounting And Finance In Partial Fulfillment Of The Requirements For The Degree Of Master Of Philosophy.